Customer Service Officers’ Ethic at PT. Avia Jaya Indah (Business Partner) PT. CPI In Pekanbaru - prihati, prihati; Elly Nielwaty (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2020)
This study aims to determine (1) How Ethics of the Customer Service Officers of PT. Avia Jaya Indah at PT. Chevron Pacific Indonesia, (2) Any obstacles in implementing Ethics in the Customer Service Officers of PT. Avia Jaya Indah at PT. Chevron Pacific Indonesia. This research method is qualitative research, after the data in the field are collected through observation, interviews and documentation, the data is clarified according to the type of data, then the data is analyzed qualitatively to describe or describe the factors that lead to the Customer Service Ethics of PT Avia Jaya Indah at PT. Chevron Pacific Indonesia in Pekanbaru is not running as it should. The results of this study indicate that (1) The overall ethics of customer service serving PT. Avia Jaya Indah is good enough and in accordance with the specified indicators, but there are still some shortcomings, such as still often found CSI employees have not used greeting generously, still often found employees who are dressed in uniform and harmonious and there are still employees who are less professional in responding to work due to lack of information and understanding of Customer Service Officers on going work in the field. (2) Obstacles that occur in implementing service ethics at PT. Avia Jaya indah is that there is still lack of professionalism in communication with customers, no follow-up regarding follow-up of requests to the customer concerned, lack of Customer Service knowledge about work in progress in the field and lack of daily evaluations of supervisor work results of customer service employees